Cyber norms: technical extensions and technological challenges. Issue 3 (2nd September 2021) - Kulikova, Alexandra
ABSTRACT: Since the late 1990s, the UN has been home to debates and negotiations on the rules, norms and principles of states' responsible behaviour in cyberspace. As these discussions matured over years, they have been taken further to different fora and have been embedded in various stakeholder initiatives. In early 2021, the Open-Ended Working Group on Developments in the Field of ICTs in the context of international security (OEWG) and the UN Group of Governmental Experts on advancing responsible state behaviour in cyberspace in the context of international security (GGE) presented their respective consensus reports, the result of over two years work. It is not only the content of this work per se that is of interest - both in what has been achieved and which parts of these mandates were less successful. These processes, historically due to the two-decades-long GGE efforts, are shaping more than just the states' commitments around cyber strategies. They help build an overarching normative environment shifting priorities in cyber risk management and contribute to the development of voluntary tech-norms, while doing this out of sync with the implications of the emerging technologies for state as well as non-state actors' accountability in cyberspace.